DNA mapping and kinetic modeling of the HrdB regulon in Streptomyces coelicolor - Šmídová, Klára; Ziková, Alice; Pospíšil, Jirí; Schwarz, Marek; Bobek, Jan; Vohradsky, Jiri (Nucleic acids research, 2019)
HrdB in streptomycetes is a principal sigma factor whose deletion is lethal. This is also the reason why its regulon has not been investigated so far. To overcome experimental obstacles, for investigating the HrdB regulon, we constructed a strain whose HrdB protein was tagged by an HA epitope. ChIP-seq experiment, done in 3 repeats, identified 2137 protein-coding genes organized in 337 operons, 75 small RNAs, 62 tRNAs, 6 rRNAs and 3 miscellaneous RNAs. Subsequent kinetic modeling of regulation of protein-coding genes with HrdB alone and with a complex of HrdB and a transcriptional cofactor RbpA, using gene expression time series, identified 1694 genes that were under their direct control. When using the HrdB-RbpA complex in the model, an increase of the model fidelity was found for 322 genes. Functional analysis revealed that HrdB controls the majority of gene groups essential for the primary metabolism and the vegetative growth. Particularly, almost all ribosomal protein-coding genes were found in the HrdB regulon. Analysis of promoter binding sites revealed binding motif at the -10 region and suggested the possible role of mono- or di-nucleotides upstream of the -10 element.
Keywords: DNA vazebné proteiny; Chromatin Immunoprecipitation; Gene Expression Regulation, Bacterial; Genes, rRNA; Kinetics; chromatinová imunoprecipitace; vazebná místa; DNA bakterií; bakteriální proteiny; modely genetické; RNA, Transfer; Bacterial Proteins; bakteriální RNA; regulon; DNA, Bacterial; sigma faktor; regulace genové exprese u bakterií; Streptomyces coelicolor; Models, Genetic; RNA, Bacterial; RNA transferová; DNA-Binding Proteins; Sequence Analysis, DNA; exprese genu; Sigma Factor; geny rRNA; promotorové oblasti (genetika); sekvenční analýza DNA; Promoter Regions, Genetic; Regulon; kinetika; Gene Expression; Binding Sites